Determination of the principal parameter of ultrasonic pulse velocity and compressive strength of lightweight concrete by using variance method - Tanyidizi, Harun; Coskun, Ahmet (Maik Nauka/Interperiodica/Springer, 2008)
Experiments are usually made to finding maximum ultrasonic pulse velocity and compressive strength of lightweight concrete. In this study, ultrasonic pulse velocity and compressive strength of lightweight concrete made with scoria aggregate, silica fume and fly ash was investigated experimentally and statistically. This article adopts Taguchi approach. The Taguchi method has been used to determine the optimum conditions and to reduce the numbers of experiments. Four control factors (maximum size of aggregate, curing conditions, mineral admixtures and curing time) for this study were used. The level of importance of these parameters on ultrasonic pulse velocity and compressive strength was determined by using analysis of variance (Anova) method.
Keywords: Fly-Ash; Pumice; Performance